2014
DOI: 10.3762/bjnano.5.158
|View full text |Cite
|
Sign up to set email alerts
|

Protein-coated pH-responsive gold nanoparticles: Microwave-assisted synthesis and surface charge-dependent anticancer activity

Abstract: SummaryThe biocompatibility and ease of functionalization of gold nanoparticles underlie significant potential in biotechnology and biomedicine. Eight different proteins were examined in the preparation of gold nanoparticles (AuNPs) in aqueous medium under microwave irradiation. Six of the proteins resulted in the formation of AuNPs. The intrinsic pH of the proteins played an important role in AuNPs with strong surface plasmon bands. The hydrodynamic size of the nanoparticles was larger than the values observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Formation of AuNPs by the reductive action of PEI under microwave irradiation was confirmed by UV/Vis extinction spectroscopy (Figure ). The strong plasmon resonance peak (SPR) at approximately λ =525 nm confirmed the formation of spherical AuNPs, a signal that was present for the whole range of w / w ratios, in accordance with the reported data . A relationship between SPR band broadening and shifting to the red upon increasing the particle size is a well‐established fact .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of AuNPs by the reductive action of PEI under microwave irradiation was confirmed by UV/Vis extinction spectroscopy (Figure ). The strong plasmon resonance peak (SPR) at approximately λ =525 nm confirmed the formation of spherical AuNPs, a signal that was present for the whole range of w / w ratios, in accordance with the reported data . A relationship between SPR band broadening and shifting to the red upon increasing the particle size is a well‐established fact .…”
Section: Resultsmentioning
confidence: 99%
“…The strong plasmon resonance peak (SPR) at approximately l = 525 nm confirmed the formation of spherical AuNPs, [27] as ignal that was present for the whole range of w/w ratios, in accordance with the reported data. [19][20][21][22][23][24][25] Ar elationship betweenS PR band broadening and shiftingt o the red upon increasing the particle size is aw ell-established fact. [26] In agreement with that, maintenance of the SPR band maximum at approximately l = 525 nm suggested that the size of the particlesd id not differ in the w/w ratio range by 1:4t o 1:128.…”
Section: Preparation and Characterization Of Aupei-npsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perspectives of new drugs development for the diagnostics and treatment of various diseases, including cancer, are associated with studies of low-dimensional nanostructures interaction with living cells [14][15][16]. The effects of colloidal gold particles [17], nanofibers or nanowires of zinc oxide [18,19], titanium oxide [20], carbon nanotubes [21] and graphene oxide [22] have been the most studied as yet. Low-dimensional structures via self-assembling can form more complex ensembles [23]; however, the interaction of cells with such ensembles can be also studied at the level of individual low-dimensional components of the complex.…”
Section: Introduction To Low-dimensional Aluminum (Hydro)oxidesmentioning
confidence: 99%
“…AuNPs possess many beneficial properties including convenience in synthesis and labelling, a large extinction coefficient, and strong surface plasmon resonance . Therefore, the application of functionalized AuNPs in biological analysis and biomedicine has attracted wide interest.…”
Section: Introductionmentioning
confidence: 99%